Ir(I)‐Catalyzed C−H Glycosylation for Synthesis of 2‐Indolyl‐C‐Deoxyglycosides. Issue 21 (7th September 2021) - Yu, Changyue; Liu, Yichu; Xie, Xiong; Hu, Shulei; Zhang, Shurui; Zeng, Mingjie; Zhang, Dan; Wang, Jiang; Liu, Hong
Abstract: The construction of 2‐deoxy‐ C ‐glycosides has gradually become a hotspot of carbohydrate chemistry in recent years. In this work, we present an efficient, regioselective, stereoselective and widely applicable strategy for the synthesis of 2‐indolyl‐ C ‐deoxyglycosides via Ir(I)‐catalyzed, pyridine‐group‐directed C−H functionalization. This method exhibits high tolerance for the functional groups of indoles and the protecting groups of carbohydrates. Moreover, this protocol has good stereoselectivity and mainly produces β ‐configuration products. Gram‐scale synthesis and several practical transformations were conducted for further applications. Meantime, we also explored the mechanism of this method and proposed a catalytic cycle Abstract :